From Composite Building to Partial Figure: Variations in the Teaching of Colin Rowe and Peter Eisenman - Michael Jasper (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This paper undertakes a comparative analysis of Colin Rowe (1920-1999) and Peter Eisenman’s (1932-) studio teaching as a form of theoretical practice. It does this through examination of select studios undertaken under their respective direction at Cornell University and the Yale School of Architecture. Three propositions underpin the paper. First, that a close reading of Rowe’s teaching reveals a specific theoretical temperament at work. Second, the paper postulates that the latent force of Rowe’s teaching is still to be fully exploited. Third, the paper suggests that one possible legacy can be seen in the studio teaching of Eisenman, arguing that Eisenman’s teaching practice and the variations on certain devices and strategies deployed by Rowe can be taken as an instance of the latter’s transformative potential. A series of questions are posed to address these propositions: Which kinds of architectural-urban problems did Rowe emphasize in his studio teaching? What concepts and composition devices were called up? What happens in the transmission and transfer through students, and the singular student of Peter Eisenman in particular? Through an analysis of their university studio teaching, the paper seeks to reveal instances of teaching practices that promote singular theoretical models, different problematics, and various composition strategies and devices which it is claimed are distinguished by their embrace of ambiguity, complexity, and multiplicity.The paper makes a contribution to scholarship on the ideas and impact of Rowe’s teaching, revealing a generative latency largely ignored in secondary literature to date. It adds to studies of twentieth-century architecture education and opens a line of research around a little studied aspect of Eisenman’s practice.